[tex]\frac{\sqrt[3]{-24}+\sqrt[3]{81}+\sqrt[3]{192}+3\sqrt[3]{-375}}{\sqrt[3]{-375}}=\frac{-2\sqrt[3]{3}+3\sqrt[3]{3}+4\sqrt[3]{3}-15\sqrt[3]{3}}{-\sqrt[3]{375}}=\\=\frac{-10\sqrt[3]{3}}{-\sqrt[3]{375}}=\frac{10}{\sqrt[3]{125}}=\frac{10}{5}=2[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\frac{\sqrt[3]{-24}+\sqrt[3]{81}+\sqrt[3]{192}+3\sqrt[3]{-375}}{\sqrt[3]{-375}}=\frac{-2\sqrt[3]{3}+3\sqrt[3]{3}+4\sqrt[3]{3}-15\sqrt[3]{3}}{-\sqrt[3]{375}}=\\=\frac{-10\sqrt[3]{3}}{-\sqrt[3]{375}}=\frac{10}{\sqrt[3]{125}}=\frac{10}{5}=2[/tex]